The Biographizme as a Factor of the Genre Creation (In the Material of the Lesia Ukrainka’s Works) - Yuliia Levchuk (Pitannâ Lìteraturoznavstva)
The article aims to explore the biographical facts as the factors of influence on the work of Lesia Ukrainka. In particular, children experience as a source of psychological complexes (relationship with mother) is regarded as one of the preconditions for the formation of dramatic thinking. Subsequently way to overcome these complexes has reached its logical conclusion by writing “The Obsessed”, thus forming a “perfect” cognitive genre model, the center of which is a drama. That is the way to forming the most organic form of genre has become central in the article. In particular, using theory of research verse, biographical and psychoanalytic methods, the author analyzed the cycles “The Journey to the Sea” (1888), “The Crimean Memories” (1890–1891) and “The Crimean Reviews” (1897–1898), and also “The Obsessed” (1901). The main attention in the research is concentrated in the analyses of work “The Winter Night in a the Foreign Country”, in which the author by the … person (Muse) mediation and the lyrical I is decide the existence problem. As a result the scientific work is ascertain, that lyrical person (what has named herself Lesia Ukrainka) can’t describe her feelings in this mode. In this way thinking a dramatist, what confirm a fact of the first place of dramatization as the mood predominance and as the special feature of thinking. Consequently, the period of Lesia Ukrainka’s creation to writing “The Obsessed” is the process subconscious searching and forming the dramatic genre, which in difference modes stay predominant during the next twelve years of literary work.